Effects of thermosyphons on the thermal regime and stability of cast‐in‐place piles in permafrost regions on the Qinghai‐Tibet Plateau. (5th April 2022) - You, Yanhui; Yu, Qihao; Wang, Xinbin; Guo, Lei; Chen, Kun; Wu, Qingbai
Abstract: The thermal effects of cast‐in‐place piles on the surrounding permafrost frequently induce deformation or failure of piles in permafrost regions. Because piles are directly inserted into the permafrost layer, the thermal disturbance of the piles is more straightforward than that of road embankments to the permafrost. Thermosyphons have proven to be effective in stabilizing the embankments of highways and railways in permafrost regions. However, the effects of thermosyphons on the thermal regime and stability of the cast‐in‐place piles remain unclear. The foundation soils of most piles in permafrost regions along the Qinghai‐Tibet Power Transmission Line were cooled by thermosyphons, and the results of a 7‐year‐period monitoring of ground temperature and deformation of a pile are presented in this paper. The results showed that the extent of thawed permafrost during the installation of the pile extended more than 5 m away from the pile. Thermosyphons shortened the refreezing time by more than 2 months. Thermosyphons cooled the surrounding permafrost to temperatures below the ambient ground temperature at the end of the cold seasons, and the temperature difference lasted until the end of the warm seasons owing to cold reserves formed in the cold season. The thermosyphons mitigated the thermal effects of the concrete pile owing to their higher thermal conductivity. Thermosyphons also significantly decreased the rate of active layer thickening around the pile compared to that observed in a natural field under a warming climate. Generally, thermosyphons stabilized the piles during the observation period by cooling the permafrost around the pile and producing a greater adfreeze force to counteract the frost heave force and subsequently support the tower. Additional thermosyphons or insulation measures may be necessary to ensure the long‐term stability of piles, considering a faster degradation of the ambient permafrost than expected. The results may provide insights into the design and maintenance of cast‐in‐place piles in warm permafrost regions.